Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/6724749
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Body Composition Relationships between Adipose Tissue Distribution and Peak Bone Mineral Density in Young Chinese Adults

Abstract: Background. The relationships between adipose tissue distribution and peak bone mineral density (BMD) in young adults are still unclear. The aim of this study was to investigate the body composition associations between fat mass (FM), lean mass (LM), regional adipose tissue distribution, and peak BMD across a cohort of young Chinese adults. Methods. Dual-energy X-ray absorptiometry (DXA) scans were performed on 786 men and 825 women aged from 20 to 40 years old to measure the markers for whole-body LM, FM, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…TF was positively correlated with BMD in the overweight group in girls and the normal-weight group in boys. Inconsistent with our finding, the majority of previous studies involving children and adolescents [8,32,33] or adults [27,34] have reported a negative relationship between TF and BMD. However, unlike our research with a wide range of body and fat mass, most of these studies were conducted in overweight or obese children.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…TF was positively correlated with BMD in the overweight group in girls and the normal-weight group in boys. Inconsistent with our finding, the majority of previous studies involving children and adolescents [8,32,33] or adults [27,34] have reported a negative relationship between TF and BMD. However, unlike our research with a wide range of body and fat mass, most of these studies were conducted in overweight or obese children.…”
Section: Discussionsupporting
confidence: 75%
“…The results of our study further demonstrate the positive relationship between FFM and BMD in children and adolescents. Because of the common genetic and hormonal determinants BioMed Research International [27,28], muscle and bone are closely related adjacent tissues [29], and loss of muscle mass and bone mass throughout life has been proven to be coupled and has been assumed to be part of the same functional unit [26]. In addition, mechanical loading increases bone formation, while weight-bearing exercise improves bone mineral stress [30].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, men who were obese had worse BMD and BMAD at the whole-body. There are established sex differences in body fat distribution where men have more visceral fat than subcutaneous fat [ 34 ]. In this study, as a surrogate measure of site-specific adiposity, we adjusted for waist and hip circumference and showed that the differences were attenuated in women but not men.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, as a surrogate measure of site-specific adiposity, we adjusted for waist and hip circumference and showed that the differences were attenuated in women but not men. Among men, fat may mainly be distributed in the trunk, but women may have a greater distribution in the limbs and hip region [ 34 , 35 ]. Women may therefore have a greater absorption of impact forces by soft-tissue padding around the hip which may translate to a bone-protective effect [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple linear regression was then used to investigate the relationship between nutritional status, physical activity level, demographic variables, and TUG performance for each gender. Due to the considerably larger sample size required for the detection of interaction effects [25], a separate regression model was built for each gender, as opposed to including gender interaction effects in one model [26,27]. Variance inflation factors (VIF) were calculated to assess for multi-collinearity (a VIF of < 4 was used as a cut-point for inclusion in the model) [28] and Durbin-Watson and Shapiro-Wilk tests were applied to the residuals to ensure assumptions of homoscedasticity and normally distributed were met, respectively.…”
Section: Statistical Analysesmentioning
confidence: 99%